THE EFFECT OF DRIP IRRIGATION ON THE INDICATORS OF THE ROOT SYSTEM AND ABOVEGROUND PART OF THE CABBAGE - Nurmatov Norqobil Jo’rayevich; Alibekov Temur Juraqulovich (Web of Journals Publishing, 2024)
This article provides data on the effect of drip irrigation on the root system and above-ground parameters of cabbage. It has been established that in the cabbage variety Termiz-2500 there is a close relationship between the growth and development of the above-ground part and root system, and that proper organization of irrigation has a positive effect on the development of the above-ground part part, the root system of plants and, as a result, increases productivity
Keywords: White cabbage, watering regimen, Drip irrigation, limited field wet capacity, developmental phases, growing period, ontogenesis.